(untitled) (JURNAL HUKUM DAS SOLLEN, 2022)
Many civil servants do not know the contents of chapter 8 PP no. 10 of 1983 in conjunction with chapter 8. PP no. 45 Year 1990. The researcher found that the ex-wife of a civil servant did not get 1/3 or ½ of her ex-husband’s salary. The judge at the Religious Court also said that he had never made a divorce decision in accordance with chapter 8 of this Government Regulation. For this reason, the researcher is interested in researching the implementation of this rule. This type of research is empirical (qualitative), the method used is a sociological juridical review in the form of descriptive. The results of this study are that so far there has been no court decision in accordance with chapter 8 of PP. 10 of 1983 jo. chapter 8 PP No. 45 Year 1990. According to information from several judges, civil servants, ex-wife of civil servants and civil servants on duty who were interviewed by the researcher, that so far the judges and civil servant agencies on duty have never made a decision as stated in Article 8 PP No. 10 of 1983 jo. PP No. 45 Year 1990, This rule is very beneficial to the wife and children, while the husband is very burdened. Obstacles in the application of chapter 8 of PP No. 10 of 1983 jo. chapter 8 PP No. 45 of 1990 caused by; People don’t know about its existence, Different Agencies, There is no legal protection yet, Husband is not willing to apply, and the rules are administrative, not rule of law. Therefore, according to the researcher, Article 8 of PP No. 10 of 1983 jo. PP No. 45 of 1990 just deleted or adapted to Islamic law as already mentioned in the Compilation of Islamic Law.